Des Teufels General - Zuckmayer, Carl 1896-1977; Eichhorn, Bernhard 1904-1980 (Kinowelt Home Entertainment, 2007)
General Harras, loosely based on the real-life Ernst Udet, is a World War I fighter ace and cynical opportunist who has accepted a post as inspector general in the Luftwaffe, despite his lack of faith in ultimate Nazi victory. When several new aircraft designs fail, the Gestapo suspects sabotage, and pressures Harras to find the culprit. Harras investigates only to find that the saboteur is his most trusted friend.
Orig.: Bundesrepublik Deutschland 1955
Keywords: Udet, Ernst <1896-1941> -- Drama; Geschichte 1941; Drittes Reich; Luftwaffe; General; Sabotage; Deutschland; Theaterstück